An analysis of slang words in the “Green Book”, a movie directed by Peter Farrelly - Diana Achmad; Nira Erdiana; Syamsul Bahri; Fany Fadilla (Universitas Syiah Kuala, 2023)
This paper aims to describe types of slang words, meanings, and reasons for using slang words in the Green Book movie directed by Peter Farrelly. The characters in the Green Book movie use slang words in their daily or informal contexts. The researchers used qualitative methods in this research process. The technique used in the data collection part was by using the observational method where the researchers observed the data collection in the form of scripts in the Green Book movie. Based on the data collection, there are 118 slang words found in this movie. The researchers concluded that there are three findings. The first finding is type of slang word where there are 4 types of slang words used by characters in the Green Book movie, such as fresh and creative, imitative, flippant, and clipping. Then, the second finding is the meaning of each slang word used by the characters in the Green Book movie. While, the third finding is the reason for using slang words where there are 7 reasons for using slang words, such as to address, to form intimate atmosphere, to initiate relax conversation, to express impression, to show intimacy, to reveal anger, and to express humiliation. This research is expected to broaden our knowledge about the slang words used in America and to widen our understanding about the application or use of slang words slang for daily life for speakers who are interested in using and learning slang words.